Configurations of Autonomy and Relatedness in a Multiethnic U.S. Sample of Parent–Adolescent Dyads. (19th June 2019) - Tran, Steve P.; Raffaelli, Marcela
Abstract : Configurations of autonomy and relatedness were explored in 232 adolescent–parent dyads. Youth (58% female) were 13–18 years old and ethnically diverse (38% Latino American, 32% European American, 30% African American). Cluster analysis was used to identify three distinct groups based on youth and parent reports of parental autonomy support and family relatedness. The three clusters differed on key demographics (e.g., parent education and income, immigrant background, ethnicity) and theoretically relevant indicators of family and individual functioning (e.g., parent and youth reports of decision making and family obligations; youth‐reported attachment and minor delinquency). Findings provide empirical support for theoretical models of autonomy–relatedness (e.g., Journal of Cross‐Cultural Psychology, 36, 2005, 403) and contribute to understanding of how autonomy and relatedness intersect to influence adolescent and family adaptation.